Orientação empreendedora : um estudo exploratório com micro, pequenas e médias empresas (MPMEs) agro industriais em Moçambique - Silva, Paulino José Paulino da (2017)
Entrepreneurial orientation (EO) is understood as a strategic posture management of organizations that is based on practices of constant innovativeness, proactiveness and risk taking. The adoption of an entrepreneurial attitude tends to raise the level of competitiveness of organizations. However, the adoption of this implies a set of conditions of several orders: economic, financial, intellectual, technological, material, etc., which theoretically are limited in micro, small and medium sized enterprises (MSMEs).Through the perspective to empirically understand this theoretical finding, the present work aimed to analyze how the dimensions of entrepreneurial orientation (innovation, proactivity and risk assumption) in the agro-industrial MSMEs in Mozambique. Based on a research of a qualitative and exploratory nature with 10 MSMEs, and through the literature review, followed by interviews, documentary analysis, content and validation by focus group, it was possible to reach the proposed objectives. The results of this research reveals the partial presence of EO elements in each dimension, which actions and effective practices more identified that demonstrate the manifestation of these elements that are related to (i) production and processing of new food crops for the innovativeness dimension; (ii) the inter-organizational partnership and the opening of new business units in the poactiveness dimension and (iii) the search for a bank financing, in the dimension of risk taking. On the other hand, the results reveal the existence of a set of internal specificities related to the organizational and external structure related to the political-legal aspects and the economic conjuncture, as being in greater negative occurrence related to its current condition of EO development.